Khalil ‘Abd Al-Karim Thought In Embodying Wasathiyyah In Muslim Indonesia To Prevent Radicalism - Mubarok, Ahmad Dliyaul; Junainawan, Dzikra; Ikmal Falahi (JASSP, 2021)
Radicalism on Muslims in Indonesia can be seen through 22 websites that contain content of radicalism. Those sites indicated teach violence and hatred against different groups, easily declared someone or a group as an apostate, spread the message of radical jihad and expand the sensitive issues such as ethnicity, religion, race and intergroup (SARA). This paper is library research using the descriptive analysis method to describe the thought of Khalil 'Abd al-Karim in realizing the wasathiyyah to Indonesian Muslims to prevent radicalism. Those notions are contextualist, flexible, no easy to declare someone or some group as apostate, and prioritize prosperity for all being. Every Muslim should preserve unity by holding fast to the god’s bond (religion) and not being divided into small fractions. The renewing concept of the Islamic law is expected to transform Indonesian Muslims to become moderate by applying the wasathiyyah (middle) concept. To create peace, justice, and spread attachment (rahmat an li al-'alamin) the concept wasathiyah is needed.